Development of a Whole Bovine Long-term Organ Culture System that Retains Vertebral Bone for Intervertebral Disc Repair and Biomechanical Studies using PrimeGrowth Media. Issue 1 (April 2016) - Grant, Michael; Epure, Laura; Salem, Omar; Alaqeel, Motaz; Antoniou, John; Mwale, Fackson
Introduction: Testing potential therapeutics in the regeneration of the disc requires the use of model systems. Although several animal models have been developed to test intervertebral disc (IVD) regeneration, application becomes costly when used as a screening method. The bovine IVD organ culture system offers an inexpensive alternative, however, in the current paradigm, the bony vertebrae is removed to allow for nutrient diffusion to disc cells. This provides limitations on the conditions and strategies one can employ in investigating IVD regeneration and mechanisms in degenerative disc disease (i.e., combination of axial and torsional loading). Although one method has been attempted to extend the survival of bovine vertebrae containing IVDs (vIVD) cell viability declined after two weeks in culture. Our goal was to develop and validate a long-term organ culture model with vertebral bone, which could be used subsequently for studying biological repair of disc degeneration and biomechanics. Material and Methods: Preparation of vIVDs: Tails of 22- to 28-month-old steers were obtained from the local abattoir within 4h of slaughter. The largest IVDs ( n = 16) were prepared for organ culture by parallel cuts through the adjacent vertebral bodies at 1 cm from the endplates using an IsoMet ® 1000 precision sectioning saw (Buehler, Germany). vIVDs were split into two groups (PrimeGrowth or DMEM): eight were treated with PrimeGrowth Media kit (developed by Intervertech and licensed to Wisent Bioproducts) and eight with DMEM. The PrimeGrowth group was incubated for 1h in PrimeGrowth Isolation Medium (Cat# 319–511-EL) and the DMEM group for 1h in DMEM. After the isolation step, discs were washed 3 times in PrimeGrowth Neutralization Medium (Cat# 319–512-CL) while the other 8 IVDs were washed thrice in DMEM. The discs isolated with PrimeGrowth and DMEM were cultured for up to 5 months in sterile vented 60 ml Leakbuster™ Specimen Containers (Starplex) in PrimeGrowth Culture Medium (Cat# 319–510-CL) and DMEM with serum and antibiotics, respectively. Culture medium was replaced every three days with no mechanical load applied. Live/Dead Assay: vIVDs cultured for 1 or 5 months were dissected to separate NP, inner AF (iAF) and outer AF (oAF) regions. A 4 mm biopsy punch was used to prepare specimens for cell viability using a live/dead fluorescence assay (Live/Dead®, Invitrogen) and visualized by confocal microscopy. Glucose Diffusion: After one month of culture, vIVDs were incubated for 72h in diffusion medium containing PBS (1x), CaCl2 (1mM), MgCl2 (0.5mM), KCl2 (5mM), 0.1% BSA and 150µM 2-[N-(7-nitrobenz-2-oxa-1, 3-diazol-4-yl)amino]-2-deoxy-D-glucose (2-NDBG), a D-glucose fluorescent analogue. Discs were dissected and NP, iAF, oAF regions were incubated in guanidinium chloride extraction buffer. Extracts were measured for fluorescence. Results: After 5 months of organ culture, vIVDs prepared with PrimeGrowth Media kit demonstrated 95% cell viability in all regions of the disc. However, dramatic reductions ( 90%) in vIVD viability were measured in DMEM-treated discs after 1 month. Interestingly, vIVD viability was related to the amount of 2-NDBG incorporated into the disc tissue. Conclusion: We have developed a novel method for isolating IVDs with vertebral bone capable of long-term viability. This method may not only help in the discovery of novel therapeutics in disc regeneration, but could also advance our understanding on complex loading paradigms in disc degeneration.